Producción de Banano orgánico var. Cavendish mediante tres formas de propagación vegetativa en Chepén, La Libertad - Bustamante Gonzáles, Lili Yanina (2019)
This work was carried out in the fields of the farmers of the CAPO CALEB Cooperative, who sow organic bananas, located in San José de Moro - Chepén - La Libertad, with the objective of investigating the production of organic Banana var. Cavendish through three forms of vegetative propagation in Chepén, La Libertad. The forms of propagation were with, corms seed, grandfathers and in vitro. The methodology used was to collect information through surveys of farmers in San José de Moro - Chepen - La Libertad. The forms of propagation were used by farmers in the same proportion, but in terms of yield, in vitro propagation was the one with the highest yield of 3,500 boxes / ha. and the one with the highest seed cost.